Can the amount of goals impact internal load in small-sided soccer games? - Mortatti, A. L.; de Oliveira, R. S. C.; Fonteles, A. I.; de Lima Pinto, J. C. B.; Junior, L. F. F.; de Sousa Fortes, L.; Costa, E. C. (Isokinetics and Exercise Science, 2019)
BACKGROUND: Small-sided games (SSG) are widely used in soccer due its potential to improve technical, tactical and physical performance. Different approaches are used to modify physical demands during SSG. Despite this, little is known about the impact of rule modifications on the internal load imposed to young soccer players. OBJECTIVE: This study aimed to compare the magnitude of the internal load imposed on young soccer players between small-sided soccer games with different amounts of goals. METHODS: Sixteen male athletes (15.7 ± 0.43 years, 64 ± 7 kg, 1.71 ± 0.05 m, 21.8 ± 1.7 kg/m 2 ) performed a SSG with one goal (SSG1 goal ) and three goals (SSG3 goal ) in a randomized order separated by 48 hours. The markers of internal load were: i) percentage of maximum heart rate (%HR) max , ii) Edward`s Training Impulse (TRIMP), and iii) performance on the repeated sprint ability (RSA) test immediately post-SSG. Paired t-test and repeated measures ANOVA were used to compare the direct (i.e. Edward`s TRIMP and HR max ) and indirect (i.e. RSA) markers of internal load between the different SSG formats. A p-value < 0.05 was set as statistically significant. RESULTS: HR max was higher in the SSG1 goal compared to the SSG3 goal (91 ± 2% vs. 89 ± 3%; p < 0.05). No difference was found in the Edward`s TRIMP (SSG1 goal : 86.4 ± 15.7 arbitrary units; SSG3 goals : 78.2 ± 12.8 arbitrary units; p = 0.15). Performance on the RSA test was worse post-SSG1 goal compared to the post-SSG3 goals (p < 0.01). SSG1 goal elicits a higher internal load than SSG3 goals . CONCLUSIONS: Therefore, the amount of goals in SSG may impact the internal load imposed on young soccer players.